Exploring Marketing Strategies To Handle Declining Occupancy In The Housing Rental Mon Property - Vinci Seflyharmi (Riviera Publishing, 2025)
The rental property market is changing rapidly across the world. Current economic fluctuations, evolving tenant needs and technological innovations are changing the competitiveness of the rental property market. This study explores the problem of Mon Property losing market share due to higher occupancy rates enjoyed by competitors offering much more attractive amenities. This is also due to competitors being digitally savvy. The company’s outdated marketing and reluctance to embrace new technology have been a problem. While competitors list property details online, provide video content and respond to frequently asked questions by prospective tenants within minutes, newer properties are attracting tenants with special offers such as car parking or public spaces and Wi-Fi. The gap between what tenants want and what the company is offering is widening. To identify solutions, this study combines tenant interviews with observational data and market insights. Today’s prospective tenants prefer hassle-free online searches, fast communication with landlords and amenities including affordable rental housing strategies. This suggests that the company is losing out to its competitive peers. These businesses are involved in building modern facilities or providing flexible rental strategies as many competitors do. The idea is to help with the occupancy decline issue but not cost too much. Suggestions include social media advertising, basic virtual tours, and quicker responses to tenant inquiries. Improvements such as building renovations or free Wi-Fi would be positive and could make the property more appealing. It also shows that modifications in traditional and digital marketing or adjustments to tenant communications can have a big impact. When competing in a crowded market, survival means finding the sweet spot between tradition and smart, affordable innovation to re-attain occupancy optimization.